IMPLEMENTASI PENYEDERHANAAN FUNGSI BOOLE DENGAN METODE QUINE McCLUSKEY - Hidayat, Alfatah; Nurshiami, Siti Rahmah; Mashuri, Mashuri (Universitas Jenderal Soedirman, 2021)
ABSTRACT. Quine McCluskey method is one method that can be used to simplify the Boolean function. The Quine McCluskey method has several advantages including having simpler, more systematic steps than other methods and it is easier to simplify the Boolean function with a large number of variables. This study discusses the design of a Boolean function simplification program for the Quine McCluskey method using Visual Basic 6.0. The resulting program can simplify the Boolean function with many variables less than equal to 26 variables and able to simplify the Boolean function in the form of Sum of Product (SOP), Product of Sum (POS), and don't care.Keywords: Boolean function, Boolean function simplification, Quine McCluskey, Visual Basic 6.0, Sum of Product, Product of Sum, don’t care. ABSTRAK. Metode Quine McCluskey merupakan salah satu metode yang dapat digunakan untuk menyederhanakan fungsi Boole. Metode Quine McCluskey memiliki beberapa keunggulan diantaranya memiliki langkah-langkah penyederhanaan yang lebih sistematis dibanding metode lain dan lebih mudah untuk menyederhanakan fungsi Boole dengan jumlah variabel besar. Penelitian ini membahas perancangan program penyederhanaan fungsi Boole metode Quine McCluskey menggunakan Visual Basic 6.0. Program yang dihasilkan mampu menyederhanakan fungsi Boole dengan jumlah variabel kurang dari sama dengan 26 variabel dan mampu menyederhanakan fungsi Boole dalam bentuk Sum of Product (SOP), Product of Sum (POS), maupun dengan kondisi don’t care. Kata kunci: fungsi Boole, penyederhanaan fungsi Boole, Quine McCluskey, Visual Basic 6.0, Sum of Product, Product of Sum, don’t care.